1974
DOI: 10.1515/bchm2.1974.355.2.1415
|View full text |Cite
|
Sign up to set email alerts
|

Mikroelektrophorese in kontinuierlichen Polyacrylamid- Gradientengelen, III[1,2]. Extraktion und Fraktionierung von Ribonucleinsäuren im Mikromaßstab

Abstract: Zusammenfassung: Kontinuierliche PolyacrylamidGradientengele von l -50% in l-, 2-, 5-und 10--Kapillaren sind zur Fraktionierung von 4S-28S-RNA geeignet. Es werden verschiedene Gel-und Puffersysteme für spezielle Trennprobleme, verschiedene Färbemethoden und Mikroextraktionsverfahren zur Präparation der RNA aus l -5 mg Gewebe angegeben. Für eine Elektrophorese genügen ca. 0.1 g einer RNA-Mischung. Kontinuierliche Puffersysteme sind besonders zur Fraktionierung hochmolekularer und diskontinuierliche zur Trennung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

1975
1975
1982
1982

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
0
6
0
3
Order By: Relevance
“…It was shown that the E. coli ribosomal 5s RNA is able to undergo conformational changes, which can be detected by gel electrophoresis [9,14]. It is therefore possible that the observed unusual electrophoretical behavior of the tRNA molecules missing their 3'-end is also due to a change in the overall shape of the molecule.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was shown that the E. coli ribosomal 5s RNA is able to undergo conformational changes, which can be detected by gel electrophoresis [9,14]. It is therefore possible that the observed unusual electrophoretical behavior of the tRNA molecules missing their 3'-end is also due to a change in the overall shape of the molecule.…”
Section: Resultsmentioning
confidence: 99%
“…Concentration of gradients was l-40% monomer at 2% crosslinking. As gel buffer 350 mM Tris-HzS04, pH 8.4 and as electrophoresis buffer 50 mM Tris-glycin, pH 8.4 was used [9] . Samples were applied on to the gel in quantities of 0.2-0.7 pmoles tRNA.…”
Section: Using Trnanucleotidy1mentioning
confidence: 99%
See 1 more Smart Citation
“…An approximate value of 1 A260 unit corresponding to 1.5 nmol of tRNA was used for calculations. The purity of tRNATy' was examined by polyacrylamide gradient gel electrophoresis according to Neuhoff [19] and on the basis of specific aminoacylation. The purification of tRNATy' in these three chromatographic steps is summarized in Table 1.…”
Section: Purification Of Trnatyrmentioning
confidence: 99%
“…Hier soll die Anwendung einer Methode (Rfichel et al [13,14], Wolfrum et al [17], Neuhoff [11]) dargestellt werden, die als Mikromethode einige Vorteile hinsichtlich des methodischen, zeitlichen und finanziellen Aufwandes besitzt und die in ihren Ergebnissen vergleichbaren Verfahren ebenbih'tig erscheint.…”
Section: Schliisselw6rter: P Olyacrylamid-gradient Engeleunclassified